Variation of European ecotypes of perennial ryegrass (Lolium perenne L.) in Poland - Schmidt , J. (Plant Breeding and Seed Science, 2005)
The creation of new perennial ryegrass varieties is impossible without instant access to wide range of natural variation i.e. to the ecotypes originating from different regions. The main goal of described experiment was to compare number of morphological, phenological and useful traits of European core collection of perennial ryegrass ecotypes in climatic conditions of Poland. Total number of 156 objects (incl. 4 standard varieties) originated from different regions of Europe were exposed to two management regimes (conservation and frequent cutting). During three subsequent years 22 qualitative and quantitative traits described variation of ‘main collection’. Further, on the basis of cluster analysis ‘sub-collection’ of 28 ecotypes from 9 clusters was selected and evaluated for 71 traits in field in similar management regimes as ‘main collection’. On the basis of described ecotypes variation it was possible to indicate following regions of ecotype origin in Europe: South Europe, West Europe, North-Middle Europe and Romania and Hungary. None of tested ecotypes exposed better yield formation than control varieties, however few ecotypes appeared to have better particular traits (better winter performance, faster spring regrowth etc.). Traits associated with inflorescence morphology (distance between florets in spikelet and distance between spikelets in spike, length of spikelet) seems to be the most stable traits, as contrary to abundance of inflorescences, tendency to produce inflorescences in year of sowing and green matter yield of first cut. High differentiation of ecotypes examined indicate existence of many botanical varieties as well as ecotypes of transition nature.